Increasing the Yield of Upland Rice in Idle Land Through Nutrient and Weed Management - Abbas, Hartinee (2006)
Recently,demand for high quality and fragrant rice has increased markedly due to affluent and health conscious consumers in Malaysia.Research on upland rice had been neglected because of low yield,despite the many good characteristics of upland rice,such as fragrance and long grains size.Furthermore,it has the advantage of cultivation on dry land without accumulation of water.Therefore,a large track of idle land in Malaysia can be developed for upland rice cultivation.This study involves the documentation of upland rice that produce high grain yield and the soil physico-chemical characteristics of idle land.A glasshouse experiment was conducted using Bukit Tuku soil (Aquic Kandiudult) and three selected upland rice varieties (Ageh, Kendinga and Strao) for determination of the optimum levels of N, P, and K fertilizer based on biomass and nutrient partitioning from the earlier survey. The experiment was carried out independently using five levels each of N, P and K with three replicates and arranged in a complete randomized design (CRD).A field trial was conducted on an idle land located in Kampung Kubang Bemban, Kuala Nerang,Kedah to evaluate the weed management practices for selected rice varieties and levels of nutrients obtained in the glasshouse study.In the field survey,35 different upland rice seeds were collected from 17 upland rice fields in Malaysia.The plant and panicle numbers and yields of upland rice varieties ranges from 10 to 18 plants hill-1, 7 to 14 panicles hill-1 and 21 to 50 g yields hill-1, respectively.Both upland rice and forest (as a control) soils were acidic,low in N content and CEC at 0-20 and 20-40 cm depths.Higher Fe content was observed in the soils; a major limitation for upland rice growth.The nutrient contents of idle land were low and higher in Al content.In the glasshouse trial, the yields of upland rice varieties ranged from 7 to 22 g hill-1 (Ageh),6 to 18 g hill-1 (Kendinga) and 9 to 22 g hill-1(Strao) depending on fertilizer types and levels.The optimum fertilizer rate for each variety was determined using different response models. Quadratic (QR) and linear (LR) response models tend to overestimate the fertilizer rates compared to LR and QR with plateau (P) response models. The fertilizer rates were 112 kg N ha-1, 78 kg P2O5 ha-1 and 158 kg K2O ha-1 for Ageh (QRP); 138 kg N ha-1 (LRP),87 kg P2O5 ha-1 (QR),119 kg K2O ha-1 (QRP) for Kendinga; and 125 kg N ha-1(QR), 85 kg P2O5 ha-1 (LRP) and 127 kg K2O ha-1 (LR) for Strao.In the field,there was heavy weed infestation in the unweeded (control) plot.Dazomet was the most effective for controlling weeds for up to 5 months after planting.Due to severe water deficit during this experiment,only estimated yield of Strao rice variety were recorded.Dazomet application at 15 x 15 cm planting distance showed higher yields (7.7 tonnes ha-1) compared to 30 x 30 cm planting distance(2.5 tonnes ha-1).Based on this study, the upland rice can be grown successfully on low land areas,such as on idle land in Peninsular Malaysia